A Study of Undergraduate Students' Performance in Nigeria - A.A. Akinrefon; A.O. Adejumo (University of Sofia, 2012)
This research work was carried out to assess undergraduate students' performance in their first year and their final year in order to ascertain which of them gives the student's true ability in his/her chosen field of study and also to investigate the effect of some variables on their final grade. The Conditional Symmetry model is used in investigating the level of agreement that exist between the students' performance in their entry year and that of their final year in the University while the multinomial logit regression is used in assessing the influence of such variables as Age, Mode of entry, Gender, First, Second, and Third year GPAs on their Final CGPA. The tau estimate from the Conditional Symmetry model showed, in all the various cross classified data, that their first year performance rated the students' performance better than their final year performance while the multinomial logit showed that the estimated odds of the student making a first/second class (up-per division) as against a second class (lower division) is higher in their first year than in the final year.